Inside Post-Socialist Courts: The Determinants of Adjudicatory Outcomes in Slovenian Commercial Disputes - Valentina Dimitrova-Grajzl; Peter Grajzl; Katarina Zajc (Center for Economic Studies and ifo Institute (CESifo), 2014)
Despite the judiciary's central role in the capitalist market system, micro-level empirical analyses of courts in post-socialist countries are remarkably rare. This paper draws on a unique hand-collected dataset of commercial claims filed at Slovenian courts to examine the determinants of two salient adjudicatory outcomes: whether a case was resolved via trial or settlement and if the case was tried, whether the plaintiff was awarded the initial claim. Consistent with the divergent expectations theory of litigation, we find that trial-based resolution is more likely when the case is complex and less likely when parties use mediation. Addressing sample selection and endogeneity concerns, we show that defendant's legal representation, plaintiff's profitability, and, importantly, court identity are robust predictors of plaintiff victory at trial. Thus, more than two decades after the start of transition in Slovenia, the judicial system is still a source of legal inconsistency and uncertainty.
Keywords: K40; K41; P37; D02; 330; courts; post-socialist countries; commercial disputes; trial; settlement